2021
DOI: 10.21037/jtd-21-1018
|View full text |Cite
|
Sign up to set email alerts
|

Pretreatment neutrophil-to-lymphocyte ratio as an important prognostic marker in stage III locally advanced non-small cell lung cancer: confirmatory results from the PROCLAIM phase III clinical trial

Abstract: Background:Neutrophil-to-lymphocyte ratio (NLR) is an important pretreatment marker of systemic inflammation and tumor aggressiveness. Increased levels of this ratio have been associated with reduced survival in several observational studies of lung cancer. However, supporting analyses from large clinical trial data are lacking. Methods:To validate the prognostic role of NLR, the current study evaluated data from a randomized phase III study (PROCLAIM; clinicaltrial.gov ID: NCT00686959) of patients with stage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Several reports have shown that peripheral blood neutrophils and T lymphocytes were activated and there were increased levels of proinflammatory cytokines in the plasma (49)(50)(51). A recent study also demonstrated that increased baseline neutrophil counts were significantly associated with worse OS but not for lymphocyte counts in NSCLC (52). Wong et al reported positive associations between white blood counts and lung cancer risk among never-smoking women (53).…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that peripheral blood neutrophils and T lymphocytes were activated and there were increased levels of proinflammatory cytokines in the plasma (49)(50)(51). A recent study also demonstrated that increased baseline neutrophil counts were significantly associated with worse OS but not for lymphocyte counts in NSCLC (52). Wong et al reported positive associations between white blood counts and lung cancer risk among never-smoking women (53).…”
Section: Discussionmentioning
confidence: 99%
“…These conventional predictors may provide valuable information that can help guide treatment decisions and improve patient outcomes. Inflammation-based prognostic marker, such as the neutrophil-to-lymphocyte ratio (NLR), lymphocyte/monocyte ratio (LMR), and platelet-to-lymphocyte ratio (PLR), have been shown to be useful in predicting survival outcomes in various types of cancer, including lung cancer, colorectal cancer, breast cancer, and ovarian cancer (39)(40)(41)(42). These indices are based on the levels of different types of cells in the blood, and can reflect the body's immune response to the cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Because circulating immune-inflammatory cells such as platelets, monocytes, neutrophils, lymphocytes, and related cytokines exert a pivotal role in local and systemic immune and inflammatory responses, researchers have investigated the prognostic and predictive significance of these cells in LA-NSCLC patients, either alone [ 8 , 9 ] or in their various blended forms [ 10 , 11 ]. Whether the index was a single cell or a unique combination of cells [ 12 , 13 ], accumulating evidence pointed to chronic systemic inflammation as a pivotal factor underlying disparities in LA-NSCLC prognoses following comparable treatment regimens [ 14 , 15 ]. The pan-immune-inflammation value (PIV), which combines circulating platelets, monocytes, neutrophils, and lymphocytes, was recently developed by Fucà et al as another comprehensive blood-borne biomarker [ 16 ].…”
Section: Introductionmentioning
confidence: 99%